ASSESSMENT OF THE SIZES OF NANOLARGE-SCALE PARTICLES OF THE LIQUIDS SPRAYED IN ELECTRIC - M. G. Verdiyev; M. K. Guseynov; Sh. Sh. Nabiyev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
A model of liquid sputtering in the electric field with a glance of environmental influence, physical qualifies of liquids and technological parameters is offered in the work. On the base of the offered model has been got a formula for counting the dimensions of liquids particles in the parameters of sputtering process, qualities of liquid and air. It is shown in the work that air influence on particles dimensions in the presence of electric potentials till 11 kw can be neglected.